1999
DOI: 10.1002/(sici)1522-726x(199909)48:1<48::aid-ccd9>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach to rotational atherectomy results in low restenosis rates in long, calcified lesions: Long-term results of the San Antonio rotablator study (SARS)

Abstract: Ablation technique and adjunctive strategy may affect restenosis after rotational atherectomy. To minimize trauma to the vascular wall, we changed the technique of rotablation as follows: the RPM range was decreased to 140,000–160,000 RPM, the ablation was performed using a repetitive pecking motion, avoiding a decrease in the rotational speed of the burr greater than 3,000 RPM, long lesions were divided into segments and each segment was separately ablated, and the burr‐to‐artery ratio was intended to be appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…35 Kiesz et al reported a low rate of restenosis of long, calcified lesions with a mean final burr-to-artery ratio of 0.73 ± 0.15. 36 In our study, we made an attempt to maintain a burr-to-artery ratio from 0.6 to 0.85, and the mean final burr-to-artery ratio was 0.74 ± 0.17. Significant burr undersizing may not ablate enough atherosclerotic plaque or calcium.…”
Section: Discussionmentioning
confidence: 99%
“…35 Kiesz et al reported a low rate of restenosis of long, calcified lesions with a mean final burr-to-artery ratio of 0.73 ± 0.15. 36 In our study, we made an attempt to maintain a burr-to-artery ratio from 0.6 to 0.85, and the mean final burr-to-artery ratio was 0.74 ± 0.17. Significant burr undersizing may not ablate enough atherosclerotic plaque or calcium.…”
Section: Discussionmentioning
confidence: 99%
“…When there was no LMCA disease among the treated lesions or when this information was missing in the article or when no systematic stenting was performed, the series was not considered. Table 5 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] presents the details and the results of the most relevant trials where rotational atherectomy was used previous to stenting and where the LMCA was almost implicated among the whole lesions of each series. The procedural successes were !90% in all the series reaching sometimes 100%.…”
Section: Methodsmentioning
confidence: 99%
“…The benefits of RA have previously been described and include improving angiographic outcomes and facilitating stent implantation in heavily calcified lesions [7-10, 21, 22] and preserving the patency of side branches in bifurcation and ostial lesions [12, 13]. In heavily calcified lesions, RA combined with a DES resulted in target lesion revascularization rates ranging from 2% to 10.6% at 6 months to 3 years of follow-up [14-18].…”
Section: Discussionmentioning
confidence: 99%